Theoretical and Numerical Study of the Flexural Behaviour of BFRP RC Beams - PAWŁOWSKI, Dawid; SZUMIGAŁA, Maciej (Engineering Transactions, 2016)
Fiber-reinforced polymer (FRP) bars have been commercially available in civil engineering in the last twenty years. Due to their mechanical and physical properties, the behaviour of FRP reinforced concrete (RC) members is significantly different to that of traditional steel RC. This paper presents the results and discussion of a numerical study of the flexural behaviour of simply supported basalt fiber-reinforced polymer (BFRP) RC beams under short-term static loads. The numerical analysis was performed using the Finite Element Method (FEM). The main objective of this paper was to investigate the flexural behaviour of BFRP RC members depending on the reinforcement ratio. The results of the numerical analysis were examined and compared with code formulations